Effect of climate change on plant regeneration from seeds in the arctic and alpine biome - Mondoni A.; Jimenez-Alfaro B.; Cavieres L. A. (Elsevier, 2022)
Alpine and arctic environments are predicted to be strongly influenced by climate change because their cold-adapted species may be sensitive to rapid warming. Genetic diversity, phenotypic plasticity, and dispersal ability of seeds might be crucial for species to persist and/or migrate in these habitats. We reviewed the literature to synthetize current knowledge on seed-trait responses to direct and indirect effects of climate warming. Most experimental and observational studies we reviewed have focused on the effects of warming on seed germination, while other seed functions have received less attention. Overall, there is compelling evidence that increasing temperatures and water stress decrease the number, size, and germination of seeds, suggesting that the net effect of warming will depend mostly on changes in water availability. These responses to climate change have been evaluated mainly in alpine temperate and arctic life zones, while alpine-tropical mountains have been largely neglected.